A DNA logic gate based on strand displacement reaction and rolling circle amplification, responding to multiple low-abundance DNA fragment input signals, and its application in detecting miRNAs. Issue 32 (23rd March 2015) - Chen, Yuqi; Song, Yanyan; Wu, Fan; Liu, Wenting; Fu, Boshi; Feng, Bingkun; Zhou, Xiang
Abstract : A conveniently amplified DNA AND logic gate platform was designed for the highly sensitive detection of low-abundance DNA fragment inputs based on strand displacement reaction and rolling circle amplification strategy. Abstract : A conveniently amplified DNA AND logic gate platform was designed for the highly sensitive detection of low-abundance DNA fragment inputs based on strand displacement reaction and rolling circle amplification strategy. Compared with others, this system can detect miRNAs in biological samples. The success of this strategy demonstrates the potential of DNA logic gates in disease diagnosis.